EMBRYO DEVELOPMENT OF YELLOWFIN TUNA (Thunnus albacares) AT DIFFERENT INCUBATION TEMPERATURE - Jhon Harianto Hutapea (Indonesian Aquaculture Journal, 2007)
The experiment was conducted in order to figure out the effect of incubation temperature on embryonic development of yellowfin tuna, Thunnus albacares eggs. Five different incubation temperatures were applied as treatments, i.e.: 24°C, 26°C, 28°C, 30°C, and 32°C with 3 replicate each. Ten micro plates with lid (IWAKI, Japan) were used; each has 6 well and 10 mL volumes. Five micro plates were used for experiment and five for balance on shaker. Three well of each micro plate were filled with 8 mL ultra violet sterilized sea water and 50 fertilized eggs. Temperature was set using Multi Thermo Incubator which has 5 level racks. Temperatures were set from the lowest to the highest on bottom to upper rack order. To maintain eggs dispersed in the medium, shaker on each rack was operated at 150 RPM. The embryo was monitored every 30-60 minutes depends on embryonic stage development using Microscope which was connected to Digital Camera DXM 1200F. Image analyses by Image Analyzer Program. The results showed, incubation temperature was significantly affect (P<0.05) embryonic development and hatching time of yellowfin tuna (Thunnus albacares) eggs. Optimum incubation temperature for embryo development and hatching was 28°C. Decreased on incubation temperature slows down embryo development at all stages, and vice versa, increased on incubation temperature accelerates embryo development.